Research assistants, reflexivity and the politics of fieldwork in urban Pakistan. Issue 1 (9th November 2016) - Anwar, Nausheen H; Viqar, Sarwat
Abstract : In this paper, we discuss the politics of fieldwork in urban Pakistan and in doing so draw attention to the role of research assistants (RAs) in the production of knowledge. The discussion explores how the roles, reflexivity and positionality of our three Muslim female RAs adds depth to our understanding of fieldwork in a culturally and politically charged urban setting where everyday violence combined with wealth asymmetries and anxieties over religious identity add layers of complexity in researcher–respondent working relationships. This generates a process of negotiation over ethical dilemmas that are not easily surmounted and complicates how we think about transformations in the production of knowledge. We use the notion of the 'triple subjectivity' of fieldwork to problematise the positionality of researchers and the people they seek to represent through translations of language, contexts and encounters. Moreover, we underscore that the positionality of our RAs was strongly influenced by religion, ethnicity and class. Notably, state directives have played an important role in the way relationships are forged in the field, whereby ethnic–religious minorities have been categorised and treated in distinct ways. Our RAs' knowledge of marginalised communities increased significantly with time spent in the field, but they still retained specific understandings of difference. This awareness was a crucial learning experience and prompted our RAs to become mindful of their own investment and contribution to the process of ethnographic engagements. Our objective in this paper is to reveal the tensions and possibilities generated by the triple subjectivities involved in our fieldwork in terms of their implications for transformations of research. Above all, our RAs' reflections demonstrate that we as researchers must remain sensitive to the emotions and anxieties of those we work alongside.